UMP Librarians conduct Information Cataloguing Workshop in Pekan - Iswan Akim, Ismail (2019)
In its continuous efforts to maintain harmonious interactions between Universiti Malaysia Pahang (UMP) and the community of Pekan, the former’s Library took on the innovative social responsibility role by conducting an “Integrated Cataloguing of Information for Resource Centres” workshop (SKBPSS) on February 13, 2019, involving several secondary schools within the district.